Phlebotomus (Adlerius) halepensis vector competence for Leishmania major and Le. tropica - Sádlová, J; Hajmová, M; Volf, P (Medical and veterinary entomology, 2003)
In Eurasia, phlebotomine sandflies of the subgenus Adlerius (Diptera: Psychodidae) comprise about 20 known species. Some are suspected vectors of visceral leishmaniasis (VL) and at least one species has been implicated as a vector of cutaneous leishmaniasis (CL). We tested Phlebotomus (Adlerius) halepensis Theodor (Jordan strain) for CL vector competence, compared with three standard vectors: Phlebotomus (Phlebotomus) duboscqi N-L. from Senegal, Phlebotomus (Paraphlebotomus) sergenti Parrot from Turkey and the Neotropical Lutzomyia longipalpis (L. & N) (Jacobina strain). Sandfly females were membrane-fed on amastigote suspensions of Leishmania major Y. & S. and Le. tropica (Wright) (Kinetoplastida: Trypanosomatidae) and examined for parasite development 3, 6 and 10 days post-infection. Phlebotomus halepensis showed high susceptibility to both leishmanias, supporting typical suprapylarian parasite development similar to the other vectors. Phlebotomus halepensis infection rates were approximately 90% for Le. major and approximately 80% for Le. tropica, with high parasite densities. Development of infections was relatively fast, colonizing the thoracic midgut by 6 days post-bloodmeal in every case and reaching the stomodeal valve in >80% of flies. In late-stage infections, 10 days post-bloodmeal, nearly all P. halepensis females had cardia and stomodeal valve filled with very high numbers of parasites and some Le. tropica-infected females had promastigotes in the pharynx and proboscis. Host choice experiments in the laboratory showed that P. halepensis females fed readily on rat or rabbit and preferred the human forearm. In view of its vector competence and partial anthropophily, we infer that P. halepensis is a potential vector of cutaneous as well as visceral leishmaniases.
Keywords: leishmanióza kožní; Feces; larva; Larva; Insect Vectors; Leishmania major; zvířata; feces; Leishmaniasis, Cutaneous; hmyz - vektory; králíci; Leishmania tropica; Phlebotomus; Rabbits; Animals